PEMBELAJARAN RANGKAIAN LISTRIK BERBASIS PROYEK UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR SISWA TL SMK N2 SAMARINDA - Setyo Prabowo, Tri; Ekohariadi, Ekohariadi; Estidarsani, Nanik (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2015)
ABSTRACT This research aims to find the differenceof activities and study achievement of the students who uses the project based learning and thosewho use direct learning process in the electrical circuit subject at SMK Negeri 2 Samarinda. This reaserch is an experimental research. The sample of the research is tenth grade of L1 as the experimental group and tenth grade of L2 as the control goup.The data is collectied through observation to find the students? learning activities, either classroom activity or practical learning activity in the garage and giving the test related to the materials comprehension of electrical circuits which consists of nuclear structures and electrical basic law to find the students? study achievement. The data analysis is perquisite test to find the homogeneity of the sample and hypothesis test to by using t test to find the difference. Based on the research, it can be concluded that (1) there is different activities of the students who uses project based learning and those who use direct learning model. The response activity in the project based is 42.86% never give response, 34.29% sometimes give response, and 22.86% often give response. For the direct learning model, there is 68.75% never give response, 22.86% sometimes give response and 8.57% often give response. The average memorizing activities in the project based is 73.571 and it is 64.143 in the direct model with t= -3.552 and the significance of 0.001. The average activity of solving the problem in the project based is 75.214 and it is 49.429 and the score of it is -5.756 and the significant of 0.000. (2) There is different study result of the students who use project based learning and those who use direct learning model. The average study achievement of the students who use project based is 76.7191 and those who use direct learning model is 72.41, the value of t is -3.112 and the significance off 0.003. Keywords: Project based learning, learning activities, and student study achievement.